Photocatalytic degradation of brilliant green and acid orange 7 in single and binary solution using TiO2 as catalyst - Noor Ilya Kosmadi (School of Environmental Engineering, University Malaysia Perlis, 2012)
The present study deals with the investigation of photocatalytic degradation of Acid Orange 7 and Brilliant Green dyes in single and binary solution effect of initial dyes concentration, dosage of catalyst, initial pH and with and without sunlight. The activity of photocatalytic used Titanium Dioxide as catalyst. Langmuir - Hishelwood kinetic model was applied to experimental data and apparent reaction rate constant were calculated. After calculation, the apparent degradation rate constant of Brilliant Green were higher than Acid Orange 7 for all experiment in single dyes solution. It was shown that photodegradation of both dyes in binary solution was slower than those in single solution under comparable conditions. The Langmuir-Hinshelwood model enabled us to satisfactorily evaluate the apparent rate constants for the degradation for single and binary solution. The kinetics of the photocatalytic oxidation follows as Langmuir-Hinshelwood model depends on several factors such as dye concentration, dosage of catalyst and pH value.